Professional and volunteer refugee aid workers–depressive symptoms and their predictors, experienced traumatic events, ptsd, burdens, engagement motivators and support needs - Borho, Andrea; Georgiadou, Ekaterini; Grimm, Theresa; Morawa, Eva; Silbermann, Andrea; Nißlbeck, Winfried; Erim, Yesim (International Journal of Environmental Research and Public Health, 2019)
In 2016, the Department of Psychosomatic Medicine and Psychotherapy of the University Hospital of Erlangen started conducting training for professional and voluntary aid workers. In total, 149 aid workers took part in the training courses, of which 135 completed the corresponding questionnaires. Engagement motivators, perceived distress in refugee work and training needs were examined. Moreover, depressive symptoms, the prevalence of traumatic experiences and symptoms of posttraumatic stress disorder were explored. Participants named helping others as the highest motivating factor for their work with refugees and communication problems as the main burden. Thirteen aid workers (10.1%) showed clinically relevant depressive symptoms. In total, 91.4% of refugee aid workers had experienced at least one traumatic event personally or as a witness but only three (3.6%) fulfilled the psychometric requirements of a PTSD diagnosis. These three participants all belonged to the professional aid workers (6.3%). More severe symptoms of depression were significantly associated with female gender (β = 0.315, p = 0.001), higher perceived burdens of refugee work (β = 0.294, p = 0.002), and a larger number of experienced traumatic events (β = 0.357, p < 0.001). According to our results, we recommend psychological trainings and regular screenings for psychological stress in order to counteract possible mental illnesses.
CRIS-Team Scopus Importer:2019-11-29
Keywords: Burdens; Depression; Engagement motivators; Germany; PTSD; Refugee aid workers; Support needs; Trainings; Traumatic experiences